Intensifiers in Bidayuh Bau-Jagoi - Campbell, Yvonne Michelle; Beon, Jill; Ting, Su-Hie (Issues in Language Studies, 2020)
This paper describes intensifiers in Bidayuh Bau-Jagoi, a variation of the Bidayuh language, spoken in Sarawak, Malaysia. Data were gathered from 10 informants, aged 50-80, who are native speakers of the Bidayuh Bau-Jagoi. In this language, intensifiers are used to intensify the meaning of expressions, particularly adjectives. Results show that intensifiers are categorised into lexical items and reduplication. Three general lexical items (sikia, manah and bonar) were identified from the data, and 86 specific lexical intensifiers were found to be paired with specific adjectives with the exception of posah and ngakag. There is only one full reduplication form where a lexical item is reduplicated (tok-tok) and it intensifies the meaning of the adjectives that precede it. As for lexical items, the intensifiers are placed after the adjective with the exception of sikia. This study has uncovered rules pertaining to the use of intensifiers in Bidayuh Bau-Jagoi that will lead to a proper and better understanding of the language structure.